2020
DOI: 10.17344/acsi.2020.5857
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Driven Photocatalytic Activity of Magnetic Recoverable Ternary ZnFe2O4/rGO/g-C3N4 Nanocomposites

Abstract: ZnFe2O4/rGO/g-C3N4 ternary nanocomposite photocatalysts with different ZnFe2O4/g-C3N4 weight ratio (0.5, 0.75, 1) were prepared by a stepwise solvothermal method using ethylene glycol as the solvent. Physicochemical methods such as X-ray diffraction, UV-Vis diffuse reflectance spectroscopy and photoluminescence spectroscopy were applied in order to characterize the composites. The formation of a meso-/macroporous structure with specific surface area between 67 and 77 m2 g–1 was confirmed by N2 adsorption/desor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It is believed that the combination of heterojunction and graphene can greatly enhance photocatalytic efficiency (Hafeez et al 2023). In 2020, Tsvetkov et al reported the ternary ZnFe 2 O 4 /rGO/g-C 3 N 4 nanocomposite (Tsvetkov et al 2020), prepared by the solvothermal method. During the photodegradation process, rGO (reduced GO) acted as an electron mediator, and efficiently separated photo-induced charge carriers (e À /h þ ), it also enhanced the adsorption ability to target pollutants.…”
Section: Spinel Ferrite/g-c 3 Nmentioning
confidence: 99%
“…It is believed that the combination of heterojunction and graphene can greatly enhance photocatalytic efficiency (Hafeez et al 2023). In 2020, Tsvetkov et al reported the ternary ZnFe 2 O 4 /rGO/g-C 3 N 4 nanocomposite (Tsvetkov et al 2020), prepared by the solvothermal method. During the photodegradation process, rGO (reduced GO) acted as an electron mediator, and efficiently separated photo-induced charge carriers (e À /h þ ), it also enhanced the adsorption ability to target pollutants.…”
Section: Spinel Ferrite/g-c 3 Nmentioning
confidence: 99%